Involvement of mTOR signaling in physiopathology and its potential therapeutic interventions - Irene Martín-Bocanegra; Thaissa Horne; Belén Maqueda-Hernández; Elena Navarro-Villarán; Jordi Muntané (Bioscientifica, 2024)
The mammalian target of rapamycin (mTOR) is a master regulator of the cell metabolism which impacts numerous signaling involved in cell proliferation and death and recycling cell constituents to readapt to new physiological or pathological environments. mTOR is constituted by two structural and functional different complexes, mTORC1 and mTORC2. Both can be independently regulated, which has a great impact on the effectiveness of therapeutic interventions in different clinical and experimental situations. Furthermore, mTORC1 interacts with specific chaperones or immunophilins which are intracellular receptors of the immunosuppressive drugs. Low and high molecular weights of immunophilins have different intracellular functions. The present review updates the molecular structure and signaling of mTOR as well as their regulation by immunophilins and upstream and downstream signaling events, highlighting the potential therapeutic intervention of mTOR in cancer, metabolic disturbances, and aging.